2021
DOI: 10.1139/cjb-2020-0113
|View full text |Cite
|
Sign up to set email alerts
|

Phytohormone requirements for pollination drop secretion in Ginkgo biloba ovules

Abstract: Secretion of the pollination drop (PD) plays a crucial role in the sexual reproduction of gymnosperms. However, the molecular mechanism regulating PD secretion has not been reported. In our study, we successfully constructed cDNA libraries in ovules between PD secretion and PD withdrawal stages, and identified 2975 differentially expressed genes (DEGs). These genes were involved in biosynthesis of secondary metabolites, fatty acid biosynthesis, fatty acid metabolism and hormone-related pathways. We especially … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…), and their expression levels are induced under MeJA treatment (Jue et al , 2018). Moreover, in Ginkgo billoba , JAZ s are downregulated in ovule and promote the secretion of pollination drops, contributing to the pollination process (Che et al , 2021). Importantly, Chen et al (2021a) found that HbCOI1 , a receptor that perceives JA, could restore male sterility and the JA response of the coi1-1 mutant inArabidopsis , implicating that they almost share a common functional JA-Ile receptor and transcriptional inhibitor JAZs to fulfil reproductive processes in herbaceous and woody plants.…”
Section: Flowering and Sterilitymentioning
confidence: 99%
“…), and their expression levels are induced under MeJA treatment (Jue et al , 2018). Moreover, in Ginkgo billoba , JAZ s are downregulated in ovule and promote the secretion of pollination drops, contributing to the pollination process (Che et al , 2021). Importantly, Chen et al (2021a) found that HbCOI1 , a receptor that perceives JA, could restore male sterility and the JA response of the coi1-1 mutant inArabidopsis , implicating that they almost share a common functional JA-Ile receptor and transcriptional inhibitor JAZs to fulfil reproductive processes in herbaceous and woody plants.…”
Section: Flowering and Sterilitymentioning
confidence: 99%